Factors affecting template switch recombination associated with restarted DNA replication - Jalan, Manisha; Oehler, Judith; Morrow, Carl A; Osman, Fekret; Whitby, Matthew C (eLife, 2019)
Homologous recombination helps ensure the timely completion of genome duplication by restarting collapsed replication forks. However, this beneficial function is not without risk as replication restarted by homologous recombination is prone to template switching (TS) that can generate deleterious genome rearrangements associated with diseases such as cancer. Previously we established an assay for studying TS in Schizosaccharomyces pombe (Nguyen et al., 2015). Here, we show that TS is detected up to 75 kb downstream of a collapsed replication fork and can be triggered by head-on collision between the restarted fork and RNA Polymerase III transcription. The Pif1 DNA helicase, Pfh1, promotes efficient restart and also suppresses TS. A further three conserved helicases (Fbh1, Rqh1 and Srs2) strongly suppress TS, but there is no change in TS frequency in cells lacking Fml1 or Mus81. We discuss how these factors likely influence TS.
Keywords: homologous recombination; replication fork collapse; RTS1; replication fork barrier; recombination-dependent replication